Laxative use and mortality in patients on haemodialysis: a prospective cohort study - Yu Honda (BMC, 2021)
Abstract Background Patients on haemodialysis (HD) are often constipated. This study aimed to assess the relationship between constipation and mortality in such patients. In this study, constipation was defined as receiving prescription laxatives, based on the investigation results of “a need to take laxatives is the most common conception of constipation” reported by the World Gastroenterology Organization Global Guidelines. Methods This cohort study included 12,217 adult patients on HD enrolled in the Japan-Dialysis Outcomes and Practice Patterns study phases 1 to 5 (1998 to 2015). The participants were grouped into two based on whether they were prescribed laxatives during enrolment at baseline. The primary endpoint was all-cause mortality in 3 years, and the secondary endpoint was cause-specific death. Missing values were imputed using multiple imputation methods. All estimations were calculated using a Cox proportional hazards model with an inverse probability of treatment weighting using the propensity score. Results Laxatives were prescribed in 30.5% of the patients, and there were 1240 all-cause deaths. There was a significant association between laxative prescription and all-cause mortality [adjusted hazard ratio (AHR), 1.12; 95% confidence interval (CI): 1.03 to 1.21]. Because the Kaplan-Meier curves of the two groups crossed over, we examined 8345 patients observed for more than 1.5 years. Laxative prescription was significantly associated with all-cause mortality (AHR, 1.35; 95% CI: 1.17 to 1.55). The AHR of infectious death was 1.62 (95% CI: 1.14 to 2.29), and that of cancerous death was 1.60 (95% CI: 1.08 to 2.36). However, cardiovascular death did not show a significant inter-group difference. Conclusions Constipation requiring use of laxatives was associated with an increased risk of death in patients on HD. It is important to prevent patients receiving HD from developing constipation and to reduce the number of patients requiring laxatives.